Cardiovascular Event Risks Associated With Masked Nocturnal Hypertension Defined by Home Blood Pressure Monitoring in the J-HOP Nocturnal Blood Pressure Study. Issue 1 (July 2020) - Fujiwara, Takeshi; Hoshide, Satoshi; Kanegae, Hiroshi; Kario, Kazuomi
Abstract : There is no information regarding the potential association between cardiovascular disease (CVD) event risks and masked nocturnal hypertension defined by home blood pressure (BP) monitoring. We sought to examine this association in a general practice population. For this purpose, we used data from the J-HOP (Japan Morning Surge-Home Blood Pressure) Nocturnal BP Study, which recruited 2745 high-cardiovascular-risk participants (mean [SD] age, 63.6 [10.4] years; 48.7% men; 82.7% on antihypertensive medications). Nocturnal home BPs (HBPs) were measured at 2:00, 3:00, and 4:00 AM using a validated, automated HBP device for 14 consecutive days. The average (SD) of nocturnal HBP measures was 17.1 (13.5). The percentages of participants with controlled BP (nocturnal HBP <120/70 mm Hg and average morning and evening BP <135/85 mm Hg), daytime hypertension (nocturnal HBP <120/70 mm Hg and average morning and evening BP ≥135/85 mm Hg), masked nocturnal hypertension (nocturnal HBP ≥120/70 mm Hg and average morning and evening BP <135/85 mm Hg), and sustained hypertension (nocturnal HBP ≥120/70 mm Hg and average morning and evening BP ≥135/85 mm Hg) were 31.7%, 7.9%, 26.7%, and 33.7%, respectively. During a median 7.6-year follow-up (19 519 person-years), 162 CVD events occurred. The cumulative incidence of CVD events was higher in those with masked nocturnal hypertension and sustained hypertension than in the controlled BP group. Results from Cox models suggested that masked nocturnal hypertension (adjusted hazard ratio, 1.57 [95% CI, 1.00–2.46]) and sustained hypertension (adjusted hazard ratio, 1.97 [95% CI, 1.26–3.06]) were associated with increased risk of CVD events. Participants with masked nocturnal hypertension defined by HBP monitoring are at high risk of future CVD events. Abstract : Supplemental Digital Content is available in the text.